Is aspirin intake associated with early age-related macular degeneration? The Singapore Indian Eye Study. Issue 6 (13th March 2013) - Cheung, Ning; Tay, Wan-Ting; Cheung, Gemmy C M; Wang, Jie-Jin; Mitchell, Paul; Wong, Tien Y
Abstract : Background/aims: To examine the relationship between aspirin intake and early age-related macular degeneration (AMD) among an Asian population. Methods: A population based cross sectional study of 3207 ethnic Indians aged 40 years or older residing in Singapore. AMD signs were graded from retinal images following the modified Wisconsin grading system. Information on aspirin intake was obtained from a standardised questionnaire. Results: The prevalence of early AMD was 5.6%. Aspirin use was reported by 11.4% of participants. Early AMD signs were present among 10.9% of aspirin users and 4.9% of non-aspirin users (p<0.001). After adjusting for potential confounders, including age, smoking and previous cataract surgery, aspirin use was associated with early AMD (OR 1.50; 95% CI: 1.01 to 2.22). The association weakened and was not significant after additional adjustment for cardiovascular disease (OR 1.38; 95% CI 0.89 to 2.14). In stratified analysis, aspirin use was significantly associated with early AMD in participants with (adjusted OR 2.64, 95% CI 1.31 to 5.36) but not without (OR 0.73; 95% CI 0.36 to 1.51) a history of cardiovascular disease (interaction term, p=0.011). Conclusions: Aspirin intake overall was not associated with early AMD in this sample of Asian Indians, but in those with a history of cardiovascular disease the association between aspirin intake and early AMD might warrant further investigation.